Risk revisited - Caplan, Patricia (London ; Sterling, Va. : Pluto Press, 2000)
Annotation Looking at the concept of risk from a cross-cultural perspective, the contributors challenge the Eurocentric frameworks within which notions of risk are more commonly considered. They argue that perceptions of danger, and sources of anxiety, are far more socially and culturally constructed - and far more contingent - than risk theorists generally admit. Topics covered include prostitutes in London; AIDS in Tanzania; the cease-fire in Northern Ireland; the volcanic eruptions in Montserrat; modernisation in Amazonia; and the BSE scare in Britain.
Introduction: Risk revisited / Pat Caplan -- The politics of risk among London prostitutes / Sophie Day -- Risk and trust: unsafe sex, gender and AIDS in Tanzania / Janet Bujra -- 'Conflicting models of risk': clinical genetics and British Pakistanis / Alison Shaw -- Risk-talk: the politics of risk and its representation / Penny Vera-Sanso -- A risky cease-fire: British infantry soldiers and Northern Ireland / Paul Killworth -- The eruption of Chances Peak, Montserrat, and the narrative containment of risk / Jonathan Skinner -- 'Eating British beef with confidence': a consideration of consumers' responses to BSE in Britain / Pat Caplan -- Risk, ambiguity and the loss of control: how people with a chronic illness experience complex biomedical causal models / Simon Cohn -- Good risk, bad risk: reflexive modernisation and Amazonia / Stephen Nugent.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Risk -- Sociological aspects; Risk perception; Risk perception -- Cross-cultural studies; Risque -- Aspect sociologique; Perception du risque; Perception du risque -- Études transculturelles; PSYCHOLOGY -- Social Psychology; POLITICAL SCIENCE -- Political Ideologies -- Democracy; Risk perception; Risk -- Sociological aspects; Risico nemen; Interculturele vergelijking; Sociologische aspecten; Cross-cultural studies